SWARM INTELLIGENCE-ENHANCED DIAGNOSIS AND THERAPY SELECTION FOR CANCER USING TUMOR- EDUCATED PLATELETS (2018)
The invention provides methods of administering immunotherapy that modulates an interaction between PD-i and its ligand, to a cancer patient, based on tumor-educated gene expression profiles obtained from anucleated cells. The invention further provides methods of typing a sample of a subject for the presence or absence of a cancer, based on tumor-educated gene expression profiles obtained from anucleated cells. The invention further provides a method for obtaining a biomarker panel for typing of a sample from a subject using particle swarm optimization-based algorithms.